2023
DOI: 10.1007/s11739-023-03203-0
|View full text |Cite|
|
Sign up to set email alerts
|

NAFLD, MAFLD, and beyond: one or several acronyms for better comprehension and patient care

Abstract: The term non-alcoholic fatty liver disease (NAFLD) has rapidly become the most common type of chronic liver disease. NAFLD points to excessive hepatic fat storage and no evidence of secondary hepatic fat accumulation in patients with “no or little alcohol consumption”. Both the etiology and pathogenesis of NAFLD are largely unknown, and a definitive therapy is lacking. Since NAFLD is very often and closely associated with metabolic dysfunctions, a consensus process is ongoing to shift the acronym NAFLD to MAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 147 publications
0
9
0
Order By: Relevance
“…53 Although prolonged fasting is associated with acute hepatic steatosis and increased insulin resistance with further lipotoxicity, 54 this was not the case in the present study, where liver transaminases remained normal, and ultrasonography did not show evidence of bright liver. 55 If Ramadan has beneficial effects on inflammation and oxidative stress in humans, is still a matter of debate, since free fatty acids and ketone bodies can have discrepant effects, and most studies have been performed in the animal models or cell lines. 21…”
Section: Effects On Metabolic Profilementioning
confidence: 99%
“…53 Although prolonged fasting is associated with acute hepatic steatosis and increased insulin resistance with further lipotoxicity, 54 this was not the case in the present study, where liver transaminases remained normal, and ultrasonography did not show evidence of bright liver. 55 If Ramadan has beneficial effects on inflammation and oxidative stress in humans, is still a matter of debate, since free fatty acids and ketone bodies can have discrepant effects, and most studies have been performed in the animal models or cell lines. 21…”
Section: Effects On Metabolic Profilementioning
confidence: 99%
“…Still, a study reporting not only LPS levels, but also LPS-binding proteins (LBP, EndoCAb IgG, EndoCAb IgM) in T1D in association with clinical risk factors is lacking. Also, no study has reported correlation of non-alcoholic fatty liver disease (NAFLD) or its surrogate markers with endotoxaemia in T1D, despite the link between MS and NAFLD 21 and the evidence of endotoxaemia in NAFLD in the general population 22 . The latter data would be of high importance, due to increasing prevalence of NAFLD in T1D and its association with complications of T1D 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the potential link of non-alcoholic fatty liver disease (NAFLD) or its surrogate markers with endotoxemia in T1D has not yet been studied. This gap in knowledge should also be filled, as there is evidence of links between MS, NAFLD [24] and endotoxemia in the general population [25]. The latter data would be of high importance due to the increasing prevalence of NAFLD in T1D and its association with the complications of T1D [26,27].…”
Section: Introductionmentioning
confidence: 99%